ANALISIS PENDAPATAN USAHATANI KOPI MITRA DAN NONMITRA DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Mabrukah, Lulu Sahar; Prasmatiwi, Fembriarti Erry; Firdasari, Firdasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This study aims to analyze the partnership patterns of coffee farmers, and compare the income of partner and nonpartner coffee farming with PT Nestle Indonesia in Tanggamus Regency. The location of this study was chosen purposively in Pulau Panggung Subdistrict. The number of samples in this study was 41 partner farmers and 32 nonpartner farmer of PT Nestle Indonesia selected using cluster random sampling. The data was collected from November 2023 to December 2023. The partnership patterns was analyzed using qualitative descriptive methods, partner and nonpartner coffee farming was analyzed using farming income analysis, and the comparison of coffee farming income between partner and nonpartner farmers was analyzed using the independent sample t-test. The study showed that the partnership patterns between coffee farmers and PT Nestle Indonesia is a general trading pattern. There is a significant difference between the average income of partner and nonpartner coffee farming in Pulau Panggung subdistrict. The average income of partner coffee farms over total costs is IDR16.112.759,71/ha/year, while non partner coffee farming income is IDR10.683.647,67/ha/year.